PEMAHAMAN MASYARAKAT CIPUTAT TERKAIT KESEHATAN MENTAL: STUDI PERBANDINGAN ZAMAN DULU DENGAN ZAMAN SEKARANG - Intan Alawiyah; Nasichah, Jundi Muhammad Fauzan, Nahda Fatiyah (CV. Adiba Aisha Amira, 2024)
Society is aware of the importance of mental health, but there is still a lack of in- depth knowledge about mental health conditions. The stigma factor still influences society's view of those who experience mental disorders. The aim of this research is to determine the understanding of the Ciputat community regarding mental health. Researchers used descriptive qualitative research methods. The data collection techniques used in this research were interviews with several sources and direct observation in the field. The results of the interview show that the Ciputat community's understanding of mental health is quite good, especially among gen z. This influences the difference in views between the understanding of ancient people and the current generation and of course this is closely related to the history of mental health. Where this can influence one of the factors in the Ciputat community's understanding of mental health.